The power of community : how phenomenal leaders inspire their teams, wow their customers, and make bigger profits - Partridge, Howard (McGraw-Hill Audio, 2018)
Howard Partridge provides a step-by-step approach to transforming an organization by tapping into the human need to connect with and feel valued by others. By creating a company culture based on core community values, listeners can empower their workforce, build customer loyalty, and drive profits and growth.